University of the Philippines Diliman, Institute of Library and Information Science Library proposed collection development program - Sampang, Rizchelle F.; Timoteo, Christine B. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study aimed to draft a collection development program for the University of the Philippines, Institute of Library and Information Science (UP ILIS). User-study and collection evaluation were conducted and the theses of Methyl A. Raca (2000) and Ruel Montes Nandwani (1998) were adopted.
User-study was employed to identify the users' needs and their information seeking behavior. Questionnaires were distributed to the sample population from the faculty members and students of the UP ILIS. Results show that all the faculty members positively communicate their information needs to the librarians. Printed books proved to be the most preferred form of information and next to it were the Internet resources, which the students have been using for 4-5 years. Majority of the faculty members use electronic journals on-line but less than half of the students use them. Faculty members and the library can help promote the usage of these resources. In general, respondents from both the faculty and students perceived the UP ILIS library collection as good.
Collection mapping was used to determine if the library collection supports the academic courses (BLIS and MLIS curricula) offered by the UP ILIS. The courses were classified using the Library of Congress Classification. Both print and non-print materials were mapped according to the courses cited to be able to identify the total number of titles and volumes per subject area. Almost all (5,978 or 99.4 percent) of the total number of titles and the total number of volumes (8378 or 99.6 percent) proved to be relevant to the LIS courses. A total of 311 titles of non-print materials were mapped.
A total of 1,119 (19.4 percent) book titles from the collection were published in the years 1991-2000. This period has the highest number of book titles acquired. In the recent years (2001-2005), however, there has been a noticeable decline in acquisition of books. This shows the trend of acquisition and then need for more recent materials especially in Information Technology (IT) courses.
Results showed that the UP ILIS Library book collection has strong support on the 12 subject areas, sufficient support on the 7 subject areas, and weak support on the 14 subject areas. Subject areas with strong support should be maintained and be improved further. Those with sufficient and weak support, more materials should be acquired.
The library has improved since the previous studies were done. A total of 2,449 titles were added to the collection, acquired recent materials, and developed some of the subject areas that were deemed sufficient and weak. Based on the PAARL Standards for Academic Libraries for 2000, the UP ILIS Library has adequate library holdings, if electronic journals will be considered. If not, the library has attained 78.3 percent (6,013 titles) of the total recommended holdings (7,680 titles).
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Institute of Library and Information Science Library -- Information resources -- User studies; University of the Philippines Institute of Library and Information Science Library -- Evaluation